AN ANALYTICAL STUDY ON METAMORPHOSIS OF DIGITALIZATION AND IT’S IMPACT ON EMPLOYEE ENGAGEMENT IN TELANGANA - Mr.Md.Sirajuddin, Dr. K. Rajesh Kumar, Dr. P. Alekhya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Information was gathered from a study of 186 respondents from different IT association situated in Telangana region. Specialist has picked exploratory as well as engaging examination plan. A few factual most of the associations in the current complex business time have understood the powerful idea of business and looking how data advances are bringing computerized change. To address the difficulties of advanced change, association needs profoundly energetic and connected with human asset at all the degree of business activities. In the present exploratory review, an endeavor is made to examine the computerized change and its effect on employees ’engagement. The vast majority of the associations in the current complex business period have understood the powerful idea of business and looking how data advancements are bringing computerized change. To address the difficulties of computerized change, association needs profoundly energetic, an endeavour is made to break down the computerized change and its effect on employees and connected with human asset at all the degree of business activities. Tests like Mean, Standard Deviation, and relapse investigation was done to survey the data pattern and examine the effect of advanced change on worker's engagement.